Development Of Learning Device Approach Realistic Mathematics To Improve Mathematical Communication Skills Of Students - Anugrah Mulia Tampubolon; Isra Suna Hasibuan; Annim Hasibuan; Yenny Suzana (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
Products of research development of this device is an educational learning realistic mathematics that is valid, practical and effective, which can improve the ability of mathematical communication students. This research aims to develop learning tools education math realistic valid, practical and effective. The research design used is 4-D. The subject of the trials in this study were students of VIII-1 and VIII-2 SMP Negeri 27 Medan T.A. 2020/2021. The results of the process of the development of these learning tools are (1) the education learning realistic mathematics and the learning included in the category of valid; (2) criteria of learning education of realistic mathematics using the learning tools included in the high category; and (3) the criteria of the effectiveness of learning tools education math realistic based on: (a) mastery learning students in the classical style of 85,71%; (b) the criteria for the attainment of the use of the learning time is included in the high category; (c) criteria for the achievement of the ability of teachers to manage the learning included in the good category; and (d) many students gave a positive response against the components and activities of the learning has been achieved.